GRAY ECONOMY IN SERBIA IN LIGHT OF TENDENCIES IN EUROPEAN COUNTRIES - Madžar, Lidija (International Journal of Economic Practice and Policy, 2014)
The gray economy presents the sum of all economic activities over which the modern state has no control, that is, which are   on the edge of the law in the so-called grey zone. It is also the part of the economy not covered by official statistics. Therefore, the gray economy is not subject to taxation and does not contribute to the gross domestic product (GDP) of the country. The aim of this paper is to present a detailed analysis of the causes and effects of this phenomenon. The paper also emphasizes the great importance of its suppression and control in modern economies. Illegal and partially legal forms of the gray economy cause tax evasion and avoiding the social security contribution payment, disrespect of valid labor standards, avoiding legal business as well as the emergence of market and structural distortions. In this paper, the problem of assessment of the gray economy is viewed through the direct and indirect measurement methods. In addition to the advantages and disadvantages, the causes of this phenomenon are set out in detail. The paper provides a comprehensive overview of ten year data on the gray economy in European countries, with concrete measures to deal with this phenomenon. The unfavorable situation of Serbian gray economy, which is worse than the European and regional average, is presented at the end of this paper.
Keywords: gray economy; tax evasion; social tendency towards the gray economy; estimation methods; cash; tax burden; regulation; tax morale